Nanoliposomal juglone/?-cyclodextrin complex as a biocontrol strategy against plant pathogenic bacteria - Bezir, Kubra; Horuz, Sumer; Acar, Serap; Cagal, Munevver Muge (Taylor & Francis Ltd, 2026)
Tomatoes are susceptible to a variety of pathogens, including bacteria, which can significantly impact plant yield and quality. The application of natural antibacterial agents, such as juglone, has shown promise in the biocontrol of these pathogens. The main objective of this study was to investigate the effects of liposomal encapsulation on enhancing the bioavailability of juglone as a biocontrol agent. The entrapment of juglone in nanoliposomes as water-soluble cyclodextrin complexes represents a novel strategy that merges the distinct advantages of these two systems into one. In this study, the juglone/beta-cyclodextrin inclusion complex was successfully encapsulated in nanoliposomes (J/beta-CD/L). Physicochemical and morphological characterizations of the formulations were conducted. The release of juglone from liposomes exhibited a cumulative release of 46.73% at 72 hours. The MIC values of the J/beta-CD/L molecule against plant pathogenic bacteria Pseudomonas syringae pv. tomato strain SH-1 (Pst), Xanthomonas euvesicatoria strain SH-2 (Xeu), and Clavibacter michiganensis subsp. michiganensis strain SH-3 (Cmm) were 68.93 mu g/mL, 34.47 mu g/mL, and 68.93 mu g/mL, respectively. These MIC values were found to be lower than free juglone. Based on the seed germination results, the prepared formulation did not show any phytotoxic effect on tomato seeds at the applied concentrations. Thus, the nanoliposomal encapsulation technique appears to be a promising method for enhancing the antibacterial effectiveness of juglone as a biocontrol agent.
Keywords: Juglone; nanoliposome; biocontrol agents; antibacterial; phytotoxicity